Pengaruh pendapatan perkapita dan jumlah penduduk serta inflasi terhadap konsumsi rumah tangga di provinsi kalimantan timur (Jurnal Ilmu Ekonomi Mulawarman (JIEM), 2020)
Kalimantan province’’. The This research aims to know the influence of Income per capita and Population as well as Household Consumption Inflation against the East Kalimantan province Year 2008-2017. This study uses secondary data obtained from the Central Bureau of statistics (BPS) year 2008-2017. Methods of analysis used in this study was Multiple Linear Regression and processed by using IBM SPSS program version 22. The data from the results it can be concluded that the author do the income per capita effect on Household Consumption of 0.974 meaning indicates a positive relationship and significance. The influence of population against the consumption of household registration 2.691 meaning indicates a positive relationship and significance. Inflation has no effect against the consumption of household registration-0.009 meaning indicates inflation has a relationship that is negative and not significant.